Use of cabotegravir in HIV prevention during pregnancy: A literature review (Research, Society and Development, 2024)
The Human Immunodeficiency Virus (HIV), the causative agent of Acquired Immunodeficiency Syndrome (AIDS), remains a significant global challenge, with millions of cases and deaths since its discovery in the 1980s, predominantly affecting women and girls. Antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) are crucial tools in the fight against HIV, with injectable cabotegravir (CAB-LA) emerging as a new long-acting PrEP option. However, the safety and efficacy of CAB-LA during pregnancy remain poorly understood, with limited data available. The objective of this study was to conduct a literature review on the safety of CAB-LA administration in pregnant women using PrEP. The methodology of this study included a comprehensive search of electronic databases, such as the National Library of Medicine (PubMed), Scopus, Embase, Web of Science, and official websites, restricted to english and portuguese languages. The results show that while CAB-LA has demonstrated good tolerance and efficacy in non-pregnant adults, its long half-life and persistence in the body, in addition to low placental transfer, present challenges for its use in pregnant women. Further studies and detailed pre-conception counseling are essential to better understand the risks and benefits of CAB-LA during pregnancy. This review indicates that until more data is available, the use of CAB-LA during pregnancy should be approached with caution and individualized consideration.